Concrete pore structure and performance changes due to the electrical chloride penetration and extraction. Issue 1 (8th March 2016) - Zheng, Li; Jones, M. Roderick; Song, Zhengtian
Abstract : Electrochemical chloride extraction (ECE) has been successfully used for reinforced concrete structure repair for those exposed to chloride environment. However, the applied external power field can cause other ionic effects on the concrete pore characteristics resulting in performance changes after treatment, especially for blended cement concretes using fly ash (FA) and ground-granulated blast furnace slag (GGBS). To evaluate this, three concrete mixes, i.e. 100%PC, 70%PC/30%FA, and 50%PC/50%GGBS with w/c ratios ranging from 0.35 to 0.55 were selected. Chloride was electrically driven into the specimens to establish chloride penetration profiles with required depth and then the ECE process was applied to remove the chloride. Pore size distributions and chloride profiles of the specimens were measured at each stage of the electrical treatment to determine any changes due to the electrical chloride penetration and extraction. Accelerated carbonation and chloride re-ingress were then carried out on the ECE-treated specimens to evaluate any changes in concrete performance. The results indicate that the applied ECE treatment obtained a very effective chloride removal. However, the micropore structure characterization shows that the capillary pores increased during both chloride penetration and ECE. The chloride penetration process aggravated carbonation resistance, and the ECE process slightly increased carbonation further. The effect of ECE process on further chloride resistance was found insignificant in pure PC and PC/FA concretes, however, not in PC/GGBS concrete. The application of a hydrophobic surface treatment to retard further chloride re-ingress has been proved to be effective.